Foundations and Practice of Security 5th International Symposium, FPS 2012, Montreal, QC, Canada, October 25-26, 2012, Revised Selected Papers - Garcia-Alfaro, Joaquin.; Cuppens, Frďřic.; Cuppens-Boulahia, Nora.; Miri, Ali.; Tawbi, Nadia. (Lecture Notes in Computer Science, 2013)
This book constitutes the carefully refereed and revised selected papers of the 5th International Symposium on Foundations and Practice of Security, FPS 2012, held in Montreal, QC, Canada, in October 2012. The book contains a revised version of 22 full papers, accompanied by 3 short papers. The papers were carefully reviewed and selected from 62 submissions. The papers are organized in topical section on cryptography and information theory, key management and cryptographic protocols, privacy and trust, policies and applications security, and network and adaptive security.